EMPATHY AND REFLEXIVITY AS DETERMINANTS OF ETHNIC TOLERANCE OF STUDENTS OF RUSSIAN AND BELARUSIAN COMMUNITIES - M. M. Karnialovich; V. I. Kazarenkov; T. B. Kazarenkova (Вестник университета)
The high applied significance of the problem of effective and tolerant student interaction in a multicultural educational environment has been proved. The results of an empirical research of personality determinants of ethnic tolerance of students have been presented. The study has been carried out on a Russian and Belarusian sample of students, which allowed us to identify specific features of the influence of empathy and reflexivity as personal determinants on the level of ethnic tolerance among students of different ethnic communities. The levels of development of empathy and reflexivity among Russian students and Belarusian students have been defined and analysed, their social predictors have been substantiated. Based on the results of variance and multiple regression analyses the strength, orientation and content characteristics of the influence of empathy and reflexivity of the individual on the student’s ethnic tolerance have been revealed. The results of the study are of interest to specialists in the field of personality psychology, ethnic psychology, cross-cultural communication.